Microfluidics and Metabolomics Reveal Symbiotic Bacterial–Fungal Interactions Between Mortierella elongata and Burkholderia Include Metabolite Exchange - Uehling, Jessie K.; Entler, Matthew R.; Meredith, Hannah R.; Millet, Larry J.; Timm, Collin M.; Aufrecht, Jayde A.; Bonito, Gregory M.; Engle, Nancy L.; Labbé, Jessy L.; Doktycz, Mitchel J.; Retterer, Scott T.; Spatafora, Joseph W.; et al. (Frontiers in Microbiology, 2019)
We identified two poplar (Populus sp.)-associated microbes, the fungus, Mortierella elongata strain AG77, and the bacterium, Burkholderia strain BT03, that mutually promote each other’s growth. Using culture assays in concert with a novel microfluidic device to generate time-lapse videos, we found growth specific media differing in pH and pre-conditioned by microbial growth led to increased fungal and bacterial growth rates. Coupling microfluidics and comparative metabolomics data results indicated that observed microbial growth stimulation involves the exchange of two ordered events. The first is an emission of fungal metabolites, including organic acids used or modified by bacteria. A second signal of unknown nature is produced by bacteria which increases fungal growth rates. We find this symbiosis is initiated in part by metabolic exchange involving fungal organic acids.